2014
DOI: 10.15429/jkomor.2014.14.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Can the Sasang Constitutional Type Trait Act as an Independent Risk Factor for Dyslipidemia?

Abstract: Objectives: This study was designed to investigate the correlation between Sasang constitution and dyslipidemia and the possibility that Sasang constitution can be a risk factor of dyslipidemia. Methods: This study was a retrospective cross-sectional study based on chart review. Seventeen thousand sixty-nine charts which were collected from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
1
6
0
3
Order By: Relevance
“…In line with this, we found a significant protective effect of high vegetable consumption on cardiometabolic risk factors in the high-risk and low-risk hs-CRP level TE groups. Several large population-based studies have reported that there is an inherent metabolic high-risk associated with the components of MetS in TE [9][10][11][12][13][14]. In particular, high BMI and obesity-related metabolic risks, such as central obesity (WC and WHR) [9,11,50], which are interrelated to the development of insulin resistance [14] and T2DM [15], were found in the TE group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, we found a significant protective effect of high vegetable consumption on cardiometabolic risk factors in the high-risk and low-risk hs-CRP level TE groups. Several large population-based studies have reported that there is an inherent metabolic high-risk associated with the components of MetS in TE [9][10][11][12][13][14]. In particular, high BMI and obesity-related metabolic risks, such as central obesity (WC and WHR) [9,11,50], which are interrelated to the development of insulin resistance [14] and T2DM [15], were found in the TE group.…”
Section: Discussionmentioning
confidence: 99%
“…Constitution type has displayed accuracy in recent studies in predicting metabolic syndrome (MetS) [9] and CVD [10]. Particularly, the Tae-eumin (TE) type showed a positive association with the components of MetS, including obesity-related factors [11][12][13][14] and T2DM [15]. Recent cohort studies have reported lower levels of adiponectin and ghrelin hormone, which act as a regulator of food intake [16], and proatherogenesis [17] in TE.…”
Section: Introductionmentioning
confidence: 99%
“…*Multiple response, † Total number was counted without in vitro studies and literary studies. (2) 관찰연구(observational study) [31][32][33][34][36][37][38]41,45,47,50) 이었으며 10편의 연구 [31][32][33][34]36,37,40,41,47,48) 에서 단일군의 특성을 확인하 였고, 10편의 연구 35,38,39,[42][43][44][45][46]49,50) 34,36,38,39,[42][43][44][45]47,48,51) 이었다. 연구 대상의 규모를 분석할 때 50명 미만이 3편 33,35,50) , 50명 이상 100명 미만이 4편 32,36,45,47) ,…”
unclassified
“…100명 이상 500명 미만이 9편 31,34,[38][39][40][41]44,48,49) , 500명 이상 1,000명 미만이 1편 39) , 1,000명 이상이 4편 37,42,43,46) 이었다.…”
unclassified
See 1 more Smart Citation